Inconstitucionalidad Del Decreto Ejecutivo 813 - Meneses Ponce, Lenny Silvana (2014)
With Executive Order 813, the government "revolutionary socialist and popular" takes one of the most disastrous policies of neoliberalism against workers called labor flexibility. Nuclear policy of structural adjustment program engineered by the Washington Consensus against the human right to have a decent job. Today Citizen Revolution in full has been fighting against the long night of neoliberalism as its spokesmen have said bombastic voice across the country and outside it, invent euphemistically buying mandatory disclaimers in the public sector. Trying a language game cheat cover the neoliberal political content of his illegitimate and illegal decision. Given the failure of the attempt that was made last year to the National Assembly amend the Public Service Act, which contemplated this labor injustice, the Executive through the Ministry of Labour Relations in an arbitrary, illegal and unconstitutional decides that applies this disastrous reform. No matter the legitimate right to decent work that every human being, regardless of the precarious situation in which workers will be made redundant without untimely public (sinceremos: compulsory renunciation is nothing that unfair dismissal), no matter the fate of the families of these workers. What is the aim of implementing this policy: reordering of spending priorities? Fiscal discipline and labor??, Job submission??, Getting rid of workers uncomfortable?;? Open jobs for workers loyal to the regime? Shrink? State size or widen it with unconditional government workers? It is difficult to know, how safe is the great harm will be done to people who are forced to sell his resignation, or perhaps better to say, with the cynicism of the government, benefiting from the purchase of your job title, the order all accounts is a good in the kingdom's capital. Even more serious is the political precedent that leaves the consciousness of the workers the possibility that their labor achievements, involving death, torture and imprisonment of hundreds, thousands of workers worldwide, are eliminated by a government that claims to be from left . It is curious to say the least that the government of the Citizen Revolution aimed, they say, is to build the Bio-Socialism of Good Living is clearly imposing unpopular policies against life and biodiversity of the country, against native peoples, against peasant villages, against working people. Policies not only violate the Constitution of 2008, in which participated, but violates basic human rights enshrined in the Universal Declaration of Human Rights, and even violate the social praxis of indigenous peoples, peasants and workers, in which flourishes within everyday new ways of living, being and being in the world, the living reality of blooms KawsaySumak, not discursive musings government technocrats drawn from their luxurious desks. Insurance technocrats who are not in the list of workers who will be laid off. The least that one can experience such a policy incoherence face, it really is a big political scam, is outrage and anger. This government is not only that many of the policies implemented unpopular that previous governments failed to do so, but also lies that governs for the people as they have made other right-wing government, but there is something worse, lying on behalf of just people's desire for change, using the emancipatory discourse of the left. This is the big political scam of capitalism at the beginning of XXI century.